2009
DOI: 10.1016/j.cgh.2009.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Myelosuppression During Thiopurine Therapy for Inflammatory Bowel Disease: Implications for Monitoring Recommendations

Abstract: Background & Aims Thiopurines (azathioprine and 6-mercaptopurine) can induce life threatening myelosuppression. To help develop rational monitoring guidelines, this study determined the frequency, timing, and outcomes of mild and severe myelosuppression following initiation of thiopurine therapy. Methods This retrospective cohort study of patients with inflammatory bowel disease patients who were new users of thiopurines; those tested for thiopurine methyltransferase levels before therapy were excluded. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 17 publications
1
56
0
Order By: Relevance
“…Another study looking at timing of myelotoxicity events in these patients though showed that the majority of events will still occur within the first 8 weeks of therapy. During this period the incidence of severe neutropenia and severe thrombocytopenia per 100 person-months was 0.51 and 0.08, respectively with a median duration from a normal white blood cell count to severe leukopenia or neutropenia of 1314 days [Lewis et al 2009]. The use of allopurinol for gout augments the risk of myelosuppression with numerous cases of profound pancytopenia reported [Kennedy et al 1996;Venkat Raman et al 1990].…”
Section: Bone Marrow Suppressionmentioning
confidence: 99%
“…Another study looking at timing of myelotoxicity events in these patients though showed that the majority of events will still occur within the first 8 weeks of therapy. During this period the incidence of severe neutropenia and severe thrombocytopenia per 100 person-months was 0.51 and 0.08, respectively with a median duration from a normal white blood cell count to severe leukopenia or neutropenia of 1314 days [Lewis et al 2009]. The use of allopurinol for gout augments the risk of myelosuppression with numerous cases of profound pancytopenia reported [Kennedy et al 1996;Venkat Raman et al 1990].…”
Section: Bone Marrow Suppressionmentioning
confidence: 99%
“…Leucopenia appeared to be the most common abnormality occurring in 3.8% and 4.6% of the patients in two large IBD cohorts 17 18. A more recent retrospective cohort study of 1997 patients reported  incidence of severe leucopenia, neutropenia and thrombocytopenia to be 0.16, 0.51 and 0.08 per 100 person-months, respectively 19. Our two cases underwent regular monitoring and did not display any preceding haematological abnormalities on blood counts.…”
Section: Discussionmentioning
confidence: 50%
“…The high incidence of severe myelosuppression justifies a frequent monitoring during the first 8 weeks of therapy. Subsequently, the rate of severe myelosuppression and the proportion of patients who progress from mild to severe myelosuppression decreases, justifying a less-frequent monitoring [42]. In the case of an abnormal white blood cell count, observation of peripheral blood smear may be useful to detect the presence of blasts, dysgranulopoiesis, dyserythropoiesis or dysmegakaryopoiesis.…”
Section: Discussionmentioning
confidence: 99%